ESTADO NUTRICIONAL E DISTÚRBIO DE IMAGEM CORPORAL EM UNIVERSITÁRIOS PRATICANTES DE MUSCULAÇÃO - Melo, Natália Mendes de; Barros Neto, João Araújo; Nascimento, Janaína da Silva; Silva, Dafiny Rodrigues; Melo, Jayanne Mayara Magalhães de; Cabral Junior, Cyro Rego (Gep News, 2017)
Tipo de Apresentação: Pôster